2016
DOI: 10.1002/2015jg003201
|View full text |Cite
|
Sign up to set email alerts
|

Catchment influence on nitrate and dissolved organic matter in Alaskan streams across a latitudinal gradient

Abstract: Spatial patterns in carbon (C) and nitrogen (N) cycles of high‐latitude catchments have been linked to climate and permafrost and used to infer potential changes in biogeochemical cycles under climate warming. However, inconsistent spatial patterns across regions indicate that factors in addition to permafrost and regional climate may shape responses of C and N cycles to climate change. We hypothesized that physical attributes of catchments modify responses of C and N cycles to climate and permafrost. We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 108 publications
11
59
1
Order By: Relevance
“…Average NO x concentrations ranged from 3.1 (Tolovana River) to 20.1 μM (Chena at Two Rivers), whereas average NH 4 + concentrations were typically an order of magnitude lower (ranging between 0.3 and 1.56 μM). Annual NOx (1.7 to 7.3 kmol N year −1 km −2 ) yields were relatively low compared to lower latitude systems (Fulweiler & Nixon, ; Meybeck, ), aligning well with values from other Arctic rivers (Harms et al, ; Holmes et al, ).…”
Section: Resultssupporting
confidence: 58%
“…Average NO x concentrations ranged from 3.1 (Tolovana River) to 20.1 μM (Chena at Two Rivers), whereas average NH 4 + concentrations were typically an order of magnitude lower (ranging between 0.3 and 1.56 μM). Annual NOx (1.7 to 7.3 kmol N year −1 km −2 ) yields were relatively low compared to lower latitude systems (Fulweiler & Nixon, ; Meybeck, ), aligning well with values from other Arctic rivers (Harms et al, ; Holmes et al, ).…”
Section: Resultssupporting
confidence: 58%
“…Along the same line, patterns in lake dissolved organic carbon (DOC) within an individual region are mainly related to lake area and perimeter (Frost et al, ), but at the global scale the main drivers are long‐term averages of precipitation, runoff and soil carbon content (Sobek, Tranvik, Prairie, Kortelainen, & Cole, ). Other studies have shown that carbon and nitrogen cycles in high‐latitude catchments have been linked to climate and permafrost at continental scales, but to watershed characteristics at regional scales (Harms et al, ). Together, these studies show the scale dependence of ecosystem‐level relationships in different regions of the globe, and here we have quantified this effect and explicitly demonstrated the importance of spatial structure in understanding ecosystem relationships at the macroscale.…”
Section: Discussionmentioning
confidence: 99%
“…Mineralized N is frequently a limiting nutrient in Arctic ecosystems (Dormann and Woodin ), the fate of which is key to understanding changes in the availability of nutrients to catchment vegetation and lake biota. Where the permafrost underlying tundra has started to thaw (e.g., North Slope of Alaska) (McClelland et al ; Harms and Ludwig ; Harms et al ), there have been dramatic changes in nutrient soil water interactions. Deepening of the active layer leads to enhanced soil organic matter decomposition rates and consequently to greater N mineralization.…”
Section: Discussionmentioning
confidence: 99%